Chemical profile of Cimicifuga heracleifolia Kom. And immunomodulatory effect of its representative bioavailable component, cimigenoside on Poly(I:C)-induced airway inflammation. (1st March 2021) - Hu, Liufang; Song, Xiaojun; Nagai, Takayuki; Yamamoto, Marina; Dai, Yi; He, Liangliang; Kiyohara, Hiroaki; Yao, Xinsheng; Yao, Zhihong
Abstract: Ethnopharmacological relevance: The dried rhizome of Cimicifuga heracleifolia Kom. ( C. heracleifolia ) is a popular traditional Chinese medicine, which has been extensively used in Asian countries for its anti-inflammatory, antipyretic and analgesic activities. However, further utilization and application of C. heracleifolia have been hampered due to a lack of full understanding of its active ingredients. Aim of study: The present study aims for clarification of the systematical chemical profile of C. heracleifolia and the immunomodulatory effect of its main bioavailable component. Materials and methods: Comprehensive chemical profile of C. heracleifolia was systematically analyzed by ultra-performance liquid chromatography hyphenated with quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF/MS). Xenobiotics after oral administration of C. heracleifolia extracts were investigated to hunt for bioavailable components. The immunomodulatory activity evaluation of cimigenoside was achieved on poly(I:C)-induced airway inflammation mouse and BEAS-2B cell models from aspects of neutrophil infiltration, lung inflammation by using microscope analysis, quantification of production and expression of inflammatory cytokine and chemokines by using ELISA and quantitative PCR. Results: By UPLC-Q-TOF/MS analysis, 110 compounds (including 81 triterpenoids, 21 cinnamic acid derivatives, and 8 other structure types) were identified or tentatively characterized in ethanolic extract of C. heracleifolia . Based on the data of chemical profile, xenobiotics of C. heracleifolia were subsequently analyzed, and triterpene glycosides were detected as the major bioavailable ingredients. Oral administration of cimigenoside, a representative triterpene glycoside, could prevent neutrophils infiltration in the lung due to suppression of the production of CXCL2 and CXCL10, and the expression of P-selectin, VCAM1 in poly(I:C)-induced airway inflammation model mice. Moreover, cimigenoside also inhibited the productions of inflammatory cytokines and chemokines from human airway epithelial cell line (BEAS-2B cells) induced by poly(I:C). Conclusion: Triterpene glycosides were the main components of C. heracleifolia extract, and cimigenoside was considered as the effective component with immunomodulatory effect on the pulmonary immune system by oral administration. Graphical abstract: Image 1 Highlights: Chemical profile of Cimicifuga heracleifolia Kom. were systematically characterized. Triterpene glycosides of Cimicifuga heracleifolia Kom. were the major bioavailable components. Cimigenoside showed a strong anti-inflammatory activity on poly(I:C)-induced airway inflammation mice model. Cimigenoside could reduce the release of inflammatory cytokines and chemokines in poly(I:C)-stimulated BEAS-2B cells.